Austrian VET policy report : progress report on developments 2002-2008 - Tritscher-Archan, Sabine [Herausgeber]; Mayr, Thomas [Herausgeber] (Institut für Bildungsforschung der Wirtschaft, 2008)
"This report is one of a set of European country reports on VET policy development. It has been produced as a contribution to Cedefop’s third policy report which reviews progress in VET towards the policy goals of the Copenhagen process. It "includes the most important information about the 'national progress in VET towards EU policy goals within the framework of the Copenhagen process and according to the policy priorities defined in the Helsinki Communiqué' [...]. The main section of this report is subdivided into seven policy areas identified by education ministers as priorities for national policy design in the VET sector [...]. The introductory chapter of this report deals with socioeconomic aspects and aspects of labour market relevance, the background of which aims to enhance understanding of national policy design. The final chapter provides an outlook of possible educational policy priorities after 2010, when the Lisbon process will be completed." (Hrsg., BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 2.2.1 Westeuropa; EU-Bildungspolitik; Berufsbildungspolitik; Berufsbildungssystem; Österreich